Combined extensive liver resections in patients with locally advanced hepatocellular cancer – clinical cases - D. V. Sidorov; M. V. Lozhkin; L. O. Petrov; A. G. Isaeva; M. S. Gusakova (Исследования и практика в медицине, 2020)
Currently the main way of curable treatment of hepatocellular carcinomas (HCC)* is a liver resection. Candidates for surgery are patient with good score of liver function (Child-Pugh A group), without destruction of great vessels and distant metastases. Hemihepatectomy is associated with a high risk of postoperative liver failure (including portal hypertension, cirrhosis, portal vein thrombosis). This reason leads to premature failure of the operation. According to current clinical guidelines, system therapy is more suitable, despite of the lack of reliable data on its effectiveness in such clinical situations. The presented cases may support the selection of advanced hemihepatectomy as a treatment for hepatocellular cancer C stage BCLC classification.